Lexicography of New Words with the Semantics of Unity and Enmity - A. V. Shchetinina (Научный диалог)
The question of the lexicographic description of new words that appeared in the Russian in the period from 2000 to 2020, the thematic groups “Unity” and “Enmity” is considered. A prospectus of an explanatory dictionary of neologisms is presented, namely: the principles of selecting nominations for registration, the structure of a dictionary entry, the rules for describing a lexical unit. It is noted that linguistic facts are registered, in the meanings of which the semes of unity and enmity are contained in the denotative part of the meaning, and words, the semantics of which is determined by the evaluative attitude of the speakers, are not recorded. The inclusion of new linguistic units in the dictionary is substantiated due to their absence in other lexicographic sources or a description in a smaller volume than is planned in the source being created. It is pointed out that the leading principles of registering new words in the dictionary being created are the activity of their use, the integrity of the description and the attitude towards the reflection of the linguistic worldview. Using the example of neologisms of different parts of speech, the structure of a dictionary entry is described, which includes, in addition to the heading word and meaning, grammatical and stylistic characteristics, information about the origin and valence, illustrative material demonstrating variants of use in speech, equivalent lexical units, antonyms and derivatives.